Cosmological constraints from galaxy clusters - Lettieri, Henrique Cardoso Naves (2022)
The Vera Rubin Observatory is one of the new experiments which will provide galaxy cluster catalogs, these catalogs will be larger and with more precise data than those currently available. Naturally, with these catalogs arises the need for development of software able to deal with the new size and precision. Moreover, the need to test different physical hypotheses requires modularized cosmological tools. Using this software we can test each model independently and include each aspect necessary to the final analyses. In our work we tested two of these cosmological frameworks, NumCosmo and CCL, which will be used by the team of researches in the LSST-DESC collaboration. These tests were be done in two parts, the first was a cross- check of the cluster counts and halo bias predictions from the two cosmological libraries. While the second part was performing a complete MCMC analysis, applying NumCosmo tools, to constraint the cosmological parameters used to create the DC2 simulation.